Blended learning strategy for engineering students in EFL class: Adoption of varied ranges of delivery procedures - Norita Prasetya Wardhani (Concept : Community Concern for English Pedagogy and Teaching, 2022)
COVID-19 Pandemic compels the teaching-learning strategy using remote learning to make the process of studying run well, including in Institut Teknologi Adhi Tama Surabaya, ITATS. A blended learning process could be applied to help the teaching-learning process. Before Covid-19 Pandemic spread in Surabaya, the students experienced fully face-to-face interaction in class. After COVID-19 existed in Surabaya, the students use the online learning process in the same semester. The highlight of this research is the case of the study which was related to the students in the teaching-learning process using blended learning in EFL class and explaining the ways how to teach and learn engineering students using blended learning. Descriptive quantitative was used to analyze the data. The data took from students' test and survey. Many students were getting difficulty in the implementation of blended learning using face-to-face strategy and google classroom. The students were allowed to access information from YouTube to make them easier to understand the materials. The lecturer was also explaining using google meet to have direct communication with the students was able to boost students’ knowledge of English materials. Adopting varied ranges of delivery procedures such as discussing was effectively boost the students' experiences and participation. Yet, those varied strategies are still ineffective rather than applying face-to-face class. Keywords: Blended-learning; online learning: learning strategies